O Melodrama Do Terror: A Índia Imaginada No Filme Mission Kashmir (2000) - Resende, Bruno Tadeu Novato [UNIFESP] (2017)
The Goal Of The Proposed Master'S Research Is To Analyze How The Film Mission Kashmir Conceives The Phenomenon Of Terrorism, And Its Stereotypes. We Intend To Understand This Phenomenon, And Its Associations To Specific Social And Confessional Groups, Based On The Assumption That Films Have An Ability To Evidence The Forms Of Representation And The Social Imaginary Of A Given Society. That Research Is Intending To Consider How Terrorism Has Been Represented In The Indian Film Mission Kashmir. To Reflect How The Militants, Their Motivations And Their Methods Of Action Are Represented In Vinod Chopra'S Feature Film, Based On The Articulation Between The Main Works Related To Terrorism And The Unavoidable Assumptions Regarding The Use Of Cinema As A Historical Source Such As Socio-Historical Analysis And The Concepts Of Representation And Social Imagination.